Impact of Socioeconomic status on Personality-driven stress and coping mechanisms (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The purpose of this quasi-experimental study was to investigate the relationship between the participants' personalities and their socio-economic status (SES) in relation to their capacity to deal with stress. One hundred and ten diploma students from Delta State University, Abraka attended the study. The use of two different types of treatment, namely Recreational Exercises treatment (RET) and Rational Emotive Behavior Therapy (REBT), was carried out using a control group design that was 3x2x2. The results did not discriminate between Type A and Type B personalities, despite the fact that personality did have a role in the decrease of stress. On the other hand, it was discovered that students who came from families with higher socioeconomic position had better abilities for dealing with stress than students who came from families with lower socioeconomic status. In addition, the Youth Coping Response Inventory (YCRI) and the Kuppuswammy socioeconomic status scale were used in a study that included 201 adolescent girls. The results of this study revealed that there were significant differences in the ways in which these girls coped with their situations based on their socioeconomic position. In contrast to their counterparts who were more adaptive, students who came from socioeconomic situations that were financially disadvantaged resorted to negative coping techniques. According to the findings, there is a pressing need for school-based counseling and support programs for children, particularly those who come from households with a lower socioeconomic position, in order to assist them in developing more effective coping skills and overall adjustment.